2001
DOI: 10.1034/j.1399-302x.2001.160107.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amino acid spacers on the antigenicity of dimeric peptide–inducing cross‐reacting antibodies to a cell surface protein antigen of Streptococcus mutans

Abstract: In the course of developing a synthetic peptide vaccine for dental caries, we identified a unique 13-mer peptide named PAc(365-377), TYEAALKQYEADL, as a minimum peptide inducing cross-inhibiting antibodies to a cell surface protein antigen (PAc) of Streptococcus mutans. However, the peptide could hardly induce the production of antibody in the absence of adjuvant. Thus using this peptide as a unit peptide, tandem constructs of dimeric unit peptide with or without spacer amino acid residues were synthesized, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…The "KK" linker was also added to prevent the epitopes between subtypes from "splitting", that is, to avoid generation of new junctional epitopes [16,17]. Based on the design of the epitope box, the nucleotide sequences were codon-optimized and the peptides synthesized accordingly (Xu Guan Biological Engineering Co., Ltd. Shanghai, PR China).…”
Section: Methodsmentioning
confidence: 99%
“…The "KK" linker was also added to prevent the epitopes between subtypes from "splitting", that is, to avoid generation of new junctional epitopes [16,17]. Based on the design of the epitope box, the nucleotide sequences were codon-optimized and the peptides synthesized accordingly (Xu Guan Biological Engineering Co., Ltd. Shanghai, PR China).…”
Section: Methodsmentioning
confidence: 99%
“…1 A) to reduce the production of antibodies against newly created epitopes created by the direct linkage of a tandem repeat (Oishi et al, 2001). R-2ϫA␤1-15 peptide, the second immunogen, contained, in addition, a three-amino-acid RGD-cell attachment motif at the N terminus, which was previously shown to increase immunogenicity and replace the use of adjuvant in combination with a different immunogen (Yano et al, 2003).…”
Section: Design and Biophysical Characterization Of Four Novel A␤1-15mentioning
confidence: 99%
“…Different spacers were also added between epitopes to study its impact on the epitope presentation (Table 2) [26][27][28][29]. Our experimental results in this study showed that an appropriate spacer between the predefined epitopes was necessary for the design of an epitope-vaccine antigen.…”
Section: Resultsmentioning
confidence: 86%